2004
DOI: 10.1016/j.vaccine.2004.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumour therapeutic efficacy of OX40L in murine tumour model

Abstract: The OX40 ligand (OX40L), a member of TNF superfamily, is a costimulatory molecule involved in T cell activation. It is expressed on antigen presenting cells including dendritic cells (DC) and activated B cells. This molecule has been reported to provide potent costimulation in APC-T cell interactions upon binding to its cognate receptor, OX40 which is expressed by activated T cells. In this study systemic administration of OX40L fusion protein was used in the treatment of established murine subcutaneous colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…This outcome is consistent with data in other systems demonstrating the enhancement of the CD8 ϩ T cell response to exogenous Ags by OX40 costimulation (20,21). Similarly, studies have shown that OX40 costimulation, given in the absence of tumor-targeted vaccination, augments antitumor immunity to poorly immunogenic tumors or tumors expressing model Ags (13)(14)(15)(16)18). In tumor-bearing FVB mice, we also observed anti-OX40 mediated enhancement of the antitumor immune response in mice given a control vaccine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This outcome is consistent with data in other systems demonstrating the enhancement of the CD8 ϩ T cell response to exogenous Ags by OX40 costimulation (20,21). Similarly, studies have shown that OX40 costimulation, given in the absence of tumor-targeted vaccination, augments antitumor immunity to poorly immunogenic tumors or tumors expressing model Ags (13)(14)(15)(16)18). In tumor-bearing FVB mice, we also observed anti-OX40 mediated enhancement of the antitumor immune response in mice given a control vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to a GM-CSF-dependent increase in the OX40 expression among CD4 ϩ and CD8 ϩ T cell subsets, we also measured an increase in the proportion of OX40-positive T cells in mice given 3T3neu/GM relative to mice vaccinated with 3T3/GM, suggesting that neu-specific T cells comprise a percentage of the OX40-positive T cells. The increased proportion of OX40-postive T cells likely underlies the synergy between GM-CSF administration and OX40 costimulation that has been reported previously (14,16). It is not yet clear whether GM-CSF directly induces OX40 expression on T cells, or whether this is an indirect consequence.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For hFcILZOX40L, inclusion of the ILZ domain may help to stabilize the OX40L trimer as well, although no direct comparison was made to extracellular OX40L domain alone. The mouse Ig:OX40L seems to function without an additional trimerizing domain (Ali et al, 2004;Morris et al, 2001), but the mouse and human sequences are quite different. Compared to the human OX40L extracellular domain, the mouse has only about 40% sequence identity, contains an additional non-homologous 13 amino acids at the C-terminus and has 1.5 times the trimer interface surface area (Compaan and Hymowitz, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In animal models for cancer and autoimmune disease, these OX40 + T cells were sorted and shown to recognize tumor or auto antigens respectively (Weinberg, 2002). Strategies to exploit the OX40-OX40L system include agonists such as anti-OX40 monoclonal antibodies or recombinant soluble OX40L, and antagonists, which include monoclonal antibodies to OX40L or OX40:Ig (alShamkhani et al, 1996;Ali et al, 2004;Weinberg et al, 1999). We have initiated a phase I clinical trial using a mouse anti-human OX40 monoclonal antibody in patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%